Responses of Capsicum annuum Varieties toward Root Knot Nematode Meloidogyne incognita Infection - Resty Islamiati Putri; Siwi Indarti; Ani Widiastuti (Jurnal Perlindungan Tanaman Indonesia, 2020)
Chili pepper (Capsicum annuum) is one of the major vegetable commodities in Indonesia. One of the challenges in chili pepper cultivation is the infection of Meloidogyne incognita which causes gall formation in root systems. The purposes of this research were to determine 1. the response of four varieties of chili pepper against M. incognita infections; 2. damaged intensity caused by this pest in the root system, and; 3. development of M. incognita populations in root systems (rhizosphere). This research was conducted in Plant Pest Science Laboratory and Greenhouse of the Department of Crop Protection, Faculty of Agriculture, University of Gadjah Mada. This research included cultivation of three chili pepper varieties (Cabai Merah Besar, Pilar F1; Cabai Merah Keriting, Kastilo F1; and Paprika, Red Star 2060), rearing of M. incognita, inoculation, and observation. Chili pepper respond to M. incognita infections were evaluated based on agronomic aspects of the plants, such as root histopathology observation, disease intensity, and nematode populations. Results showed that each variety of chili pepper expressed various responses to infections. All varieties had different root weight and length, but had similar sensitivity based on the appearance of root damage and egg mass scoring of M. incognita. Although nematode population could develop on roots, observation from root tissues showed lignification after infection of J2 M. incognita. Chili pepper var. Red Star 2060 was more susceptible against M. incognita than chili pepper var. Pilar F1 and chili pepper var. Kastilo F1.